TRENDS IN THE DEVELOPMENT OF THE MARKET FOR NEW EDUCATIONAL TECHNOLOGIES - I. V. Kramarenko (Вестник университета)
Questions related to education and its quality are always relevant. The growing momentum of online education raises many questions for participants in the educational process, in particular, the choice of a platform provider of online services, the development of educational content, the placement and updating of online resources, the promotion of educational content among users, etc. The typology and characteristics of the market of online educational technologies have been presented in the article, trends of its further development have been defined. The classification and brief description of Russian and foreign platform providers implementing online training have been given. The forms of education, where the special place is given to adaptive education and development of self-education possibility have been considered. The tendencies of the Internet development as a necessary element of the online learning system have been revealed.